(untitled) (New York, 2003)
Helps students to: Increase their scientific literacy and improve their critical thinking abilities, acquire mastery of a diverse subset of scientific concepts, develop positive attitudes about science, become comfortable reading graphs and interpreting their meaning, learn to use computers and other modern technologies with skill and confidence.
Keywords: Physics,Explorations